PENGARUH KOMPONEN RGEC PADA PERUBAHAN HARGA SAHAM PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Hendrayana, Putu Wira; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 11 No 1 (2015), 2015)
Level of bank health is an important aspect that should be known by the bank and its stakeholders. Level of bank health is an important aspect that should be known by the bank and its stakeholders. In addition to maximizing the function of the bank as intermediary, bank health assessments are also able to provide a signal or the ease in making investment decisions. In 2011, the health of banks assessed using RGEC. Research on the health assessment of banks to make use of indicators RGEC not been done so interesting to study. Research on the health assessment of banks to make use of indicators RGEC not been done so interesting to study. Samples that have been selected will be analyzed using multiple linear regression. Years of research were in the range of 2011-2012 with the initial reason RGEC enforcement. The results showed that there is a positive and significant relationship GCG and ROA on the stock price changes, while there is a negative and significant relationship of risk profiles and CAR on stock price changes. Based on the research results RGEC factors as indicators of bank health assessment is able to have an impact on the stock price changes that banking company go public. The results of this study are expected to provide information to the bank's internal order to always maintain the health of their banks and users of external reporting may consider indicators RGEC in making investment decisions.
Keywords: Risk Profile, Good Corporate Governance, Earning, Capital, stock price